Analisis Karakter Organisasi Tenaga Kependidikan UNIKA De La Salle Manado menggunakan Macroergonomic Organizational Questionaire Survey - Tryadi; Ronald Albert Rachmadi (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2020)
Organizational culture is a system of disseminating trust and values that develops in an organization and directs the behavior of its members. De La Salle Catholic University of Manado is one of the educational institutions that has the motto "Religio, Mores, Cultura", in Latin which means religious, social, and culture. A good organizational culture will certainly make the conditions of the work environment, as well as the relationship between workers to be better which will eventually produce a good result as well. So far there has never been an evaluation of the condition of the current university organization. Therefore, it is necessary to identify and assess the influence of organizational culture characteristics on the current state of the organization with the Macroergonomic Organizational Questionnaire Survey (MOQS) approach. Organizational cultural characteristics that will be used as research variables according to Stephen P. Robbins namely Innovation and risk taking, Attention to detail, Outcome orientation, People Orientation, Team Orientation, Aggressiveness, and Stability. This study resulted in the contribution of each independent variable (X) to the dependent variable (Y) asOrganization and representing the Organizational Culture that was built as follows, Innovation and risk taking : 0,10%., Attention to : 1,18%., Outcome orientation : 0,16%., People orientation : 0,06% ,Team Orientation : 65,44%., Aggressiveness : 29,206% , Stability : 31,92%.